E-Learning Gamelan Ensemble Playing Techniques (Jurnal Seni Musik, 2021)
2020 is a very challenging year because of the covid-19 pandemic and this completely changed the music education landscape. In the past, learning musical instruments could be done face to face, now it is impossible. If no action is taken, this situation could cause stress among students, especially those who learning gamelan ensemble instruments. Unlike other musical instruments, the ensemble gamelan is expensive and student cant afford to buy it. That is why set of gamelan is only owned by the university and placed in the faculty only. Due to this, students who live far away are unable to practice their gamelan instrument due to movement control order these days. Therefore, this study introduces Gamelan E-Learning Techniques, which is the concept of learning gamelan basic hand techniques using a simulation methods for keromong, gambang, saron and gendang. The uniqueness of this study is due to the emphasis on the basic hand techniques of gamelan. By using google class application as well, lecturers can upload learning videos as well as assessment of student game techniques online can be done. This study uses experimental case study method with qualitative approach. The participants consisted of second semester of 36 students who attended the AME 3082 gamelan course at Universiti Pendidikan Sultan Idris (UPSI).